Effectiveness of the program for restoring the function of the upper limb in traumatic and compression-ischemic injuries of the peripheral nerves and brachial plexus - Оlena Bismak (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effectiveness of the developed program for the restoration of upper limb function in traumatic and compression-ischemic injuries of the peripheral nerves. Material & Methods: the study involved 173 patients who were divided into 2 main rehabilitation groups: group I - patients with acute traumatic damage to the peripheral nerve or plexus (132 people), group II - patients with compression-ischemic (tunnel) neuropathies and plexopathies (41 people). The study was conducted on the basis of the Institute of Neurosurgery acad. A. P. Romodanova of the National Academy of Medical Sciences of Ukraine" (2015-2018) and on the basis of neurological departments No. 1 and No. 2 of the Kiev City Clinical Hospital No. 4 (2017-2019). To assess impaired motor function of the nerve and sensitivity, a 6-point scale was used according to the method of R. B. Zachary, W. Holmes, N. Millesi. The Boston Questionnaire (Boston Carpal Tunnel Questionnaire) was used to assess the severity of symptoms, activity, and participation in daily life. Results: during the initial examination, we found that in the majority of patients of the 1st rehabilitation group, motor disorders on a 6-point scale were at the level of M1-M2 in 27,3% and 31,8% of individuals, respectively, and M3 in 15,9% of patients. In patients of the rehabilitation group II, the indicators of motor disorders were not so pronounced: patients with impaired motor function at the level of M2-M3 prevailed (34,1% and 24,4% of patients, respectively). According to the scale of functional disorders of the Boston questionnaire, the patients with the studied groups experienced the greatest difficulties when bathing and putting on clothes - 17,4%, doing homework - 13,6% of people, fastening buttons on clothes - 15,2%. In patients of the rehabilitation group II, approximately the same results were observed. In the main group, we used the program of rehabilitation measures that we developed, in the comparison group, the program that is used in the hospital for this category of patients. The therapy lasted 3 months. Upon repeated examination in patients of the main І rehabilitation group, motor disorders decreased under the influence of physical therapy, which were used in them. In the main group, a greater number of patients (12,3%) showed normal strength in the affected limb (M5), in the control group this indicator was lower (7,5%). Movements with overcoming the weight of the limb (M3) and movements with overcoming the resistance (M4) were observed in 24,6% and 30,8% of patients in the main group, which significantly exceeds similar indicators of the control group. Conclusions: as shown by the results of studies, physical therapy and occupational therapy in the complex treatment of people with traumatic and compression-ischemic neuropathies of the upper limb contributed to a more intensive restoration of arm functions and increased results of motor therapy. The following rehabilitation measures are most effective for this category of patients: kinesiotherapy, taping, massage, physiotherapy, mechanotherapy and hydrotherapy.